(untitled) (Research, Society and Development, 2022)
The objective of this research was to verify the relationship between handball and school in the lives of students/athletes and technical teachers who represented the city of Curitiba in the Paraná Youth Games, from the perspective of the Bioecological Theory. Study methodology, the research had a qualitative approach with an exploratory and descriptive nature. In the data analysis, we used the technique of content analysis (BARDIN, 2016) of the interviews carried out with the ten students/athletes and the 5 technical/teachers. Results and Discussion, it was pointed out that although the good relationship between handball and school is fundamental, there is a lack of support from the school context to the handball context and the educational aspects have transcended the context of the modality and school. Final Considerations shows that the practice of handball in the city of Curitiba, Paraná is largely carried out in the school environment, so both contexts must be complementary and not competing.